Comprehensive model of metadislocation movement in Al13Co4. (15th March 2015) - Heidelmann, M.; Heggen, Marc; Dwyer, Christian; Feuerbacher, Michael
Abstract : Metadislocations are highly complex defects mediating plasticity in several complex metallic alloys. Available models characterizing the atomic rearrangements during the movement of these defects are limited to two dimensions and heavy atomic species. Combining high-resolution scanning transmission electron microscopy, density functional theory and simulated annealing we develop a three-dimensional model of a metadislocation glide step of 12.3 Å in the complex metallic alloy Al13 Co4 including all atomic species. The rearrangements within the core are shown to involve maximum atomic jump distances of 3.4 Å.